Improvement of measurement method for hydroxylated polychlorinated biphenyls (OH-PCBs) in blood samples using LC/MS/MS - Tobiishi, Kazuhiro; Suzuki, Shigeru; Todaka, Takashi; Hirakawa, Hironori; Hori, Tsuguhide; Kajiwara, Jumboku; Hirata, Teruaki; Iida, Takao; Uchi, Hiroshi; Furue, Masutaka (Fukuoka igaku zasshi = Hukuoka acta medica, 2013)
Hydroxylated polychlorinated biphenyls (OH-PCBs) are well known as metabolites of PCBs in the human body. We improved a measurement method for OH-PCBs in blood samples using LC/MS/MS. A new 2 microm particle column was used, and the analytical conditions for the LC/MS/MS measurements were optimized. The improved method is more sensitive than the conventional method for 5g blood samples. And, this method is effective at determining the concentrations of OH-PCBs, PCBs and dioxins from the same sample without special treatment of the sample such as derivatization.